Proceedings of the Phythochemical Society of Europe - Proceedings of the Phythochemical Society of Europe (Kluwer Academic, 2000)
This book deals with the latest in the field of polysaccharides and related products and their biological activities, especially the immunological effects. It also describes the structure and bioactivity of polysaccharides from plants used in traditional medicine in different parts of the world, especially China, Japan and Europe